Directions for improving the regulatory framework for the use of discretionary powers by law enforcement agencies in administrative legal relations - O. A. Prysiazhniuk (Bulletin of Kharkiv National University of Internal Affairs)
The article notes that limiting the discretionary powers of law enforcement agencies through the implementation of legislative provisions which would detail and set the limits for the application of these powers is seen as one of the primary tasks for these institutions to comply with the rule of law and is considered to be the main leitmotif of the process of improving the regulatory framework for the use of discretionary powers by law enforcement agencies in administrative legal relations.